Antibiotic Prophylaxis in Torso, Maxillofacial, and Skin Traumatic Lesions: A Systematic Review of Recent Evidence - Enrico Cicuttin; Massimo Sartelli; Emanuele Scozzafava; Dario Tartaglia; Camilla Cremonini; Bruno Brevi; Niccolò Ramacciotti; Serena Musetti; Silvia Strambi; Mauro Podda; Fausto Catena; Massimo Chiarugi; et al. (MDPI AG, 2022)
Use of antibiotic prophylaxis (AP) in trauma patients is a common practice. However, considering the increasing rates of antibiotic resistance, AP use should be questioned and limited only to specific cases. We performed a systematic review of recent literature (from year 2000), aiming to summarize the state of the art on efficacy and appropriateness of AP in patients with traumatic injuries of torso, maxillofacial complex and skin (including burns). Twenty-six articles were selected. In thoracic trauma, AP could be useful in reducing infective complications in tube thoracostomy for penetrating trauma. In maxillo-facial trauma, AP could find a role in the peri-operative trauma setting in the case of a graft or prosthetic implant. In abdominal trauma, there is a lack of consensus on the definition of contamination, infection, antibiotic therapy, and prophylaxis. In burned patients, routine AP is not suggested. In the case of human bites to the extremities, AP could find an indication. Future studies should focus on the subcategories of patients at higher risk of infection, identifying those who would benefit from AP. Attention to antimicrobial stewardship and guidelines focused on AP in trauma are required, to reduce antibiotic abuse, and increase quality research.